Elderly Sami as the "Other": Discourses on the Elderly Care of the Sami, 1850–1930 - Liliequist, Marianne; Karlsson, Lena (Journal of Northern Studies, 2012)
In this article, the authors have examined images of elderly Sami in relation to elderly care in Sweden between the years 1850 and 1930. What discourses can be revealed from spoken statements, written documents and everyday practices? This study has shown that the higher the degree of closeness and mutual exchange between Sami and non-Sami, the more the image of the “Other” as something “foreign” has been challenged and rejected. To be able to one-sidedly distance oneself from other people and turn them into stereotypes requires a certain amount of emotional and geographic distance. Where there has been physical distance and a lack of mutually beneficial exchange, the elderly Sami are more often described as “foreign,” “threatening” and “deviant,” a force of nature that must be tamed and controlled. The Sami dismissed as “not-quite-human” in the popular discourse were the paupers among them. A more balanced relationship existed between the Sami and the settlers in the mountains and the elderly Sami were often described as “one of the family.” The staffs of the Sami old-age homes were far more nuanced in their view of the elderly than the civil servants sent from Stockholm to report back on the Sami.